Green marketing and the purchasing decision oriented towards sustainable consumption - Salguero Núñez, Cristian Stalin (2024)
Sustainable and environmentally friendly consumption is a current trend, so marketing strategies focused on this doctrine have taken its name green marketing or green marketing. The present research is oriented to analyze green marketing from the perspective of sustainable consumption, for this purpose a correlational study was used between the two variables of green marketing study mediated by four dimensions: sustainability, price, quality, and durability proposed in four scenarios of purchase decision, segmenting consumers by age, gender, economic and social status and level of education. The main results show that women tend to buy sustainable products regardless of their level of education and that young people are the age groups that show the greatest interest in environmental care. The correlation matrix reflects that the male gender is more inclined to price and quality of products rather than sustainability. Low, medium, and high economic and social status are inclined towards the purchase scenario where sustainability goes hand in hand with price, quality, and durability of products.